Oxidative trimerization of indoles via water-assisted visible-light photoredox catalysis and the study of their anti-cancer activities. Issue 32 (31st July 2020) - Cheng, Li-Ting; Luo, Sheng-Qi; Hong, Bor-Cherng; Chen, Chia-Ling; Li, Wen-Shan; Lee, Gene-Hsiang
Abstract : The water-promoted visible-light photoreaction of indole was demonstrated, and the indolinones synthesized were evaluated for their anti-cancer activities. Abstract : Incorporation of water has been revealed to successfully facilitate visible-light photoredox catalysis of indole leading to increased production of C2-quaternary indolinone. The water-promoted photoreaction of indole under catalyst-free conditions by a household compact fluorescence light was also demonstrated. The antiproliferative activity of the synthesized indolinones was evaluated against three human cancer cell lines.